Analysis Of The Implementation Of Pancasila Values Through Civics Education (PKN) Learning In Junior High Schools: A Literature Review - Iba, Lenny; Iba, Susance (Lembaga Riset dan Inovasi Almatani, 2026)
This study aims to analyze the implementation of Pancasila values through Civics Education (PKn) learning at the junior high school (SMP) level using a literature review approach. The research employs a qualitative method with data collected from various scientific sources, including journals, books, and previous research findings. Data analysis was conducted by identifying, categorizing, and synthesizing findings related to the implementation of Pancasila values in PKn learning. The results indicate that the implementation of Pancasila values in PKn learning still faces several challenges, including the dominance of cognitive-oriented approaches, limited innovation in teaching methods, and insufficient integration of values into contextual learning practices. However, several studies also reveal that active, contextual, and experiential learning models, such as project-based learning and group discussions, can enhance students’ internalization of Pancasila values. Furthermore, school environment, teacher role modeling, and positive school culture significantly contribute to the success of value implementation. This study concludes that the implementation of Pancasila values through PKn learning should be carried out holistically by integrating cognitive, affective, and psychomotor aspects, supported by innovative teaching strategies and a conducive educational environment.